You're nobody 'til somebody kills you [large type] - Randisi, Robert J. (Randisi, Robert J. Rat Pack mystery series., 2010)
It's not really a rat pack member who needs help from Eddie G., pit boss at the Sands Casino, but an extended family member. Marilyn Monroe, still smarting from being blamed for Clark Gable's death after the filming of The Misfits, thinks she's being followed. Eddie's up for the job, but when he gets word that his mother has died, Eddie must leave buddy P. I. Danny Bardini to look after Marilyn.